Effect of the residential areas of geriatrics living in turkey on physical activity, depression, and quality of life during the covid-19 pandemic - ŞENOCAK, EMRE; YILDIZ ÖZER, AYSEL (My University, 2022)
Objective: The quarantine precautions implemented during the new type of coronavirus epidemic caused some changes in the daily lives of geriatric individuals. This study aimed to examine whether living in rural or urban areas affects physical activity, depression, and quality of life (QoL) in Turkish geriatrics during pandemic. Method: One hundred three geriatrics were assessed with the videoconferencing method, which was performed once. Participants were divided into two groups according to the area where they lived as rural (n:41) or urban (n:62). In addition, physical activity, presence of depression, and QoL of individuals were assessed with the Physical Activity Scale for the Elderly (PASE), Geriatric Depression Scale (GDS), and Short Form-36 (SF-36), respectively. Results: According to the results, PASE (p=0.677), GDS (p=0.742), and all sub-dimensions of SF-36 (p>0.05 for all) except pain (p=0.033) of geriatrics were similar in both groups. Also, while there is a low-level relationship between the GDS scores of those living in rural areas and the sub-dimensions of SF-36 physical function (r=- 0.381), mental health (r=-0.381), and social functionality (r=-0.395), there was a moderate correlation between the vitality (r=-0.529) and pain (r=-0.536) sub-dimensions. In addition, a strong correlation was found between GDS and the general health perception sub-dimension of SF-36 (r=-0.611). Conclusion: The pandemic-induced quarantine precautions, which were put into effect throughout Turkey, negatively affected the daily life of all people, especially elderly individuals. Because of these precautions, the similarity of daily living activities of the elderly living in rural and urban areas may have caused similar physical activity, depression, and QoL scores.

Amaç: Yeni tip koronavirüs salgını sırasında uygulanan karantina önlemleri, yaşlı bireylerin günlük yaşamlarında bazı değişikliklere neden oldu. Bu çalışma, pandemi süresince kırsal veya kentsel alanlarda yaşamanın Türkiye’deki yaşlı bireylerin fiziksel aktivite, depresyon ve yaşam kalitesini etkileyip etkilemediğini incelemeyi amaçlamıştır. Yöntem: Yüz üç yaşlı birey, bir kez yapılan video konferans yöntemiyle değerlendirildi. Katılımcılar yaşadıkları bölgeye göre kırsal (n:41) ve kentsel (n:62) olarak iki gruba ayrıldı. Bireylerin fiziksel aktivite, depresyon varlığı ve yaşam kaliteleri sırasıyla Yaşlılar İçin Fiziksel Aktivite Ölçeği (YFAÖ), Geriatrik Depresyon Ölçeği (GDÖ) ve Kısa Form-36 (KF-36) ile değerlendirildi. Bulgular: Sonuçlara göre yaşlıların YFAÖ (p=0.677), GDÖ (p=0.742) ve KF-36'nın ağrı (p=0.033) dışındaki tüm alt boyutları (tümü için p>0.05) her iki grupta benzerdi. Ayrıca kırsal kesimde yaşayanların GDÖ puanları ile KF-36 fiziksel işlev (r=-0.381), ruh sağlığı (r=- 0.381) ve sosyal işlevsellik alt boyutları (r=-0.395) arasında düşük düzeyde bir ilişki varken, canlılık (r=-0.529) ve ağrı (r=-0.536) alt boyutları arasında orta düzeyde bir ilişki vardı. Ek olarak, KF-36'nın genel sağlık algısı alt boyutu ile GDÖ arasında güçlü bir ilişki bulundu (r=-0.611). Sonuç: Türkiye genelinde uygulamaya konulan pandemi kaynaklı karantina önlemleri başta yaşlılar olmak üzere tüm insanların günlük yaşamını olumsuz etkiledi. Bu önlemler nedeniyle kırsal ve kentsel alanlarda yaşayan yaşlıların günlük yaşam aktivitelerinin benzerliği, benzer fiziksel aktivite, depresyon ve yaşam kalitesi skorlarının oluşmasına neden olmuş olabilir.
Covid-19 pandemisi sürecinde türkiye’de yaşayan yaşlı bireylerin yaşam alanlarının fiziksel aktivite, depresyon ve yaşam kalitesine etkisi
Keywords: Covid-19; Geriatrics; Physical Activity; Depression; Yaşlı; Fiziksel Aktivite; Depresyon